ZnO–ferromagnetic metal vertically aligned nanocomposite thin films for magnetic, optical and acoustic metamaterials. Issue 1 (12th December 2022) - Paldi, Robynne L.; Kalaswad, Matias; Lu, Juanjuan; Barnard, James P.; Richter, Nicholas A.; Si, Mengwei; Bhatt, Nirali A.; Ye, Peide D.; Sarma, Raktim; Siddiqui, Aleem; Huang, Jijie; Zhang, Xinghang; et al.
Abstract : Magnetoacoustic waves generated in piezoelectric and ferromagnetic coupled nanocomposite films through magnetically driven surface acoustic waves present great promise of loss-less data transmissions. Abstract : Magnetoacoustic waves generated in piezoelectric and ferromagnetic coupled nanocomposite films through magnetically driven surface acoustic waves present great promise of loss-less data transmission. In this work, ferromagnetic metals of Ni, Co and Co x Ni1− x are coupled with a piezoelectric ZnO matrix in a vertically-aligned nanocomposite (VAN) thin film platform. Oxidation was found to occur in the cases of ZnO–Co, forming a ZnO–CoO VAN, while only very minor oxidation was found in the case of ZnO–Ni VAN. An alloy approach of Co x Ni1− x has been explored to overcome the oxidation during growth. Detailed microstructural analysis reveals limited oxidation of both metals and distinct phase separation between the ZnO and the metallic phases. Highly anisotropic properties including anisotropic ferromagnetic properties and hyperbolic dielectric functions are found in the ZnO–Ni and ZnO–Co x Ni1− x systems. The magnetic metal–ZnO-based hybrid metamaterials in this report present great potential in coupling of optical, magnetic, and piezoelectric properties towards future magnetoacoustic wave devices.